2019
DOI: 10.1089/g4h.2018.0126
|View full text |Cite
|
Sign up to set email alerts
|

Dark Play of Serious Games: Effectiveness and Features (G4HE2018)

Abstract: Objective: Choosing inappropriate or unethical actions in games is referred to as dark play. For a serious game on delirium for medical students, we aimed to investigate the potential differences between dark play and normal play on game effectiveness regarding abilities in advising care, learning motivation and engagement, and attitude toward delirious patients. Furthermore, we aimed to explore the use of different game features between the two types of play on empathy, self-efficacy, and consequences of care… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

1
9
0

Year Published

2020
2020
2024
2024

Publication Types

Select...
5
1
1

Relationship

1
6

Authors

Journals

citations
Cited by 14 publications
(10 citation statements)
references
References 24 publications
1
9
0
Order By: Relevance
“…Yet, our results imply that engaging in different simulation situations in The Delirium Experience (eg, the severity of the delirious episodes) does not result in differences in lessons learned or self-reported knowledge. This is in line with the results of our previous study showing that normal or dark play did not affect game effectiveness in students who were allocated to the two conditions [ 19 ].…”
Section: Discussionsupporting
confidence: 92%
See 1 more Smart Citation
“…Yet, our results imply that engaging in different simulation situations in The Delirium Experience (eg, the severity of the delirious episodes) does not result in differences in lessons learned or self-reported knowledge. This is in line with the results of our previous study showing that normal or dark play did not affect game effectiveness in students who were allocated to the two conditions [ 19 ].…”
Section: Discussionsupporting
confidence: 92%
“…Although many studies on serious games in medical education have been reported in recent years [ 16 - 18 ], these studies often investigated serious games as whole artifacts without focusing on the effect of different play strategies such as dark play. In a previous study, we showed that dark play did not affect game effectiveness [ 19 ]. However, our students had been allocated to a normal or dark play condition without being able to choose their game.…”
Section: Introductionmentioning
confidence: 99%
“…Tele-empathy is a promising emerging field where clinicians and carers can get a sense of what the patient is experiencing physically, such as tremors in Parkinson’s disease ( Palanica et al, 2019 ). Research on serious games for medical education (The Delirium Experience) shows certain game features, being able to “switch perspective,” can enhance medical student empathy if they play the game from the patient or nurse perspective ( Buijs-Spanjers et al, 2019 ; Ma et al, 2021 ). Experiments in the Netherlands on a serious game for care workers for people with disabilities (The world of EMPA) showed participation did not enhance empathy for disabled people but it did decrease personal distress in care workers ( Sterkenburg and Vacaru, 2018 ).…”
Section: Resultsmentioning
confidence: 99%
“…It was shown in one of the included studies that a voluntarily poor decision making in an SG compared with a "normal" one did not influence the improvement of cognitive skills [SMD = 0.00 (95% CI = −0.31 to 0.31)]. 51 Another study showed that more frequent but lighter sessions of SG usage led to higher knowledge acquisition than fewer but more intensive sessions of SG usage [SMD = 0.43 (95% CI = 0.30 to 0.56)]. 53 The last one focused on the evaluation of 2 similar SGs; the experimental group received an SG an educational content aligned with the learning objectives as the control group received an SG with a similar, but irrelevant educational content, to avoid compensatory equalization in this group.…”
Section: Descriptive Results Of Included Studiesmentioning
confidence: 99%
“…Few included studies compared different versions of an SG between one another, which is essential to isolate the impact of individual design choices. 47,51,52,72 Future studies should focus on evaluating the efficacy of different versions of an SG on engagement and learning outcomes.…”
Section: Discussionmentioning
confidence: 99%